OsWRKY93 Dually Functions Between Leaf Senescence and in Response to Biotic Stress in Rice - Li, Yanyun; Liao, Shuting; Mei, Pengying; Pan, Yueyun; Zhang, Yu; Zheng, Xiangzi; Xie, Yakun; Miao, Ying (Frontiers in Plant Science, 2021)
Cross talking between natural senescence and cell death in response to pathogen attack is an interesting topic; however, its action mechanism is kept open. In this study, 33 OsWRKY genes were obtained by screening with leaf aging procedure through RNA-seq dataset, and 11 of them were confirmed a significant altered expression level in the flag leaves during aging by using the reverse transcript quantitative PCR (RT-qPCR). Among them, the OsWRKY2, OsWRKY14, OsWRKY26, OsWRKY69, and OsWRKY93 members exhibited short-term alteration in transcriptional levels in response to Magnaporthe grisea infection. The CRISPR/Cas9-edited mutants of five genes were developed and confirmed, and a significant sensitivity to M. oryzae infection was observed in CRISPR OsWRKY93-edited lines; on the other hand, a significant resistance to M. oryzae infection was shown in the enhanced expression OsWRKY93 plants compared to mock plants; however, enhanced expression of other four genes have no significant affection. Interestingly, ROS accumulation was also increased in OsWRKY93 enhanced plants after flg22 treatment, compared with the controls, suggesting that OsWRKY93 is involved in PAMP-triggered immune response in rice. It indicated that OsWRKY93 was involved in both flag leaf senescence and in response to fungi attack.